Reestructuring the 5S program in a furniture industry (Revista Brasileira de Contabilidade e Gestão, 2021)
The goalof this paperis to describe the process of restructuring the 5S methodology applied in a furniture industry. The researchwas developed in three phases: i. survey of the problem; ii. process restructuring; iii. training theteams. The 5S evaluationprocess was restructured, and several training sessions were carried out with the company's teams, improvingthe results of 5S audits in the organization. The researchconfirmed the importance of commitment of all employees; the importanceof the organization's leadership and management alignmentwith the project, and the application of a clear and transparent evaluation method for the success of the 5S methodology. The steps presented in the paper, as well as the evaluation method and the proposed 5S committee can be applied in other organizations, highlighting the research’s contribution.
Keywords: Lean Manufacturing; Kaizen; Industry; 5S